Evaluation of rheology property of dodecyl maltoside, sucrose dodecanoate, Brij 35p and SDS stabilized O/W emulsion: Effect of head group structure on rheology property and emulsion stability - Niraula, B.; King, T.C.; Misran, M. (2004)
Emulsifying property of four emulsifiers is being explored and compared using tensiometry and Rheology. These emulsifiers possess same number of carbon in their alkyl tail (C 12 in this case), but differ in their head group structure. The head group structure of these emulsifiers are maltose, sucrose, ethylene oxide and sulphate; providing a homologue series whose head group polarity and therewith HLB values differ significantly from each other. While aqueous emulsifier solutions of varying concentration were used as water phase, paraffin oil was used as oil phase. The oil to water mixing ratio used was 8:2. This naturally gave rise to high internal phase concentrated oil-in-water (O/W) emulsions with dispersed phase volume fractions of â0.8, in which the dispersed droplets are organized to give a densely packed polyhedron configuration as described by Princen. Such concentrated emulsions would exhibit interesting Rheology properties including shear-thinning behavior and viscoelastic effects. Given all other factors such as procession conditions (energy input through shearing and shearing time), volume fraction of the dispersed phase and viscosity of the continuous phase kept constant, the given mixing ratio would yield oil-in-water emulsions whose droplet size distribution and polydispersity index depended strongly on HLB value of the emulsifier used for their emulsification. The Rheology properties of such emulsions strongly depended on the average size distribution of the dispersed droplets that could be varied both with the bulk concentration and HLB value of the emulsifier. The interfacial and surface properties of these surfactants suggest that the droplet size distribution of the dispersed phase is strongly related to the HLB value and bulk concentration of the emulsifier used. Hence, it is evident that the Rheology properties of such emulsions vary strongly both with the HLB value and bulk concentration of the emulsifier. That is why the Rheology properties can be employed to describe both the emulsifying effect of the emulsifier and the storage stability of the resulting emulsion. As expected, the emulsifying effect of the emulsifier, the structure of the resulting emulsions and their storage stability depended strongly on HLB value of the emulsifier. As identified by yield stress, shear viscosity and storage modulus, both the degree of emulsification and storage stability enhanced with decreasing droplet size of the dispersed phase, and decreased with decreasing HLB value of the emulsifier used. Both the emulsifying effect and emulsion stability further were enhanced with increasing emulsifier concentration.